HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V DI SD NEGERI 24 TANJUNG BUNGA - Devi Efa Naibaho; Regina Sipayung; Darinda Sofia Tanjung (Universitas Negeri Medan, 2020)
This study aims to determine the level of learning discipline at SD Negeri 24 Tanjung Bunga and its relationship with students learning outcomes. The sample in the study consisted of 32 students. The method of research used is descriptive-correlational. The instrument used to measure the discipline of study was a questionnaire which consisted of 30 items. Meanwhile, the value of the results of the report cards semester of even years of teachings in 2020 was used to measure the outcomes of learning. The results obtained that the value of the mean (average) score of the questionnaire amounted was 120,5. It means that the students studying discipline at SD Negeri 24 Tanjung Bunga are at a higher level. To determine the level of relationship between the disciplinary study with the results of the study, the formula of the Pearson correlation wasapplied. From the calculation results, r was 0.752, which means that the correlation value is strong/correlated. Test of significance was applied to test the hypothesis by comparing the value of t arithmetic with t table. It was obtained that the value of t = 6.248 while the t table = 1.697. Because t count ≥ t table (6,248 ≥ 1,697), Ho was accepted and Ha was rejected. Throught test, it can be concluded that there is a significant relationship between thestudentslearning discipline and students learning outcomes.Key words: relationship students learning discipline, students learning outcomes